Diterpenoid fingerprints in pine foliage across an environmental and chemotypic matrix: Isoabienol content is a key trait differentiating chemotypes. (March 2018) - Kännaste, Astrid; Laanisto, Lauri; Pazouki, Leila; Copolovici, Lucian; Suhorutšenko, Marina; Azeem, Muhammad; Toom, Lauri; Borg-Karlson, Anna-Karin; Niinemets, Ülo
Abstract: Diterpenoids constitute an important part of oleoresin in conifer needles, but the environmental and genetic controls on diterpenoid composition are poorly known. We studied the presence of diterpenoids in four pine populations spanning an extensive range of nitrogen ( N ) availability. In most samples, isoabienol was the main diterpenoid. Additionally, low contents of ( Z )-biformene, abietadiene isomers, manoyl oxide isomers, labda-7, 13, 14-triene and labda-7, 14-dien-13-ol were quantified in pine needles. According to the occurrence and content of diterpenoids it was possible to distinguish 'non diterpenoid pines', 'high isoabienol pines', 'manoyl oxide – isoabienol pines' and 'other diterpenoid pines'. 'Non diterpenoid pines', 'high isoabienol pines' and 'other diterpenoid pines' were characteristic to the dry forest, yet the majority of pines (>80%) of the bog Laeva represented 'high isoabienol pines'. 'Manoyl oxide – isoabienol pines' were present only in the wet sites. Additionally, orthogonal partial least-squares analysis showed, that in the bogs foliar nitrogen content per dry mass ( N M ) correlated to diterpenoids. Significant correlations existed between abietadienes, isoabienol and foliar N M in 'manoyl oxide – isoabienol pines', and chemotypic variation was also associated by population genetic distance estimated by nuclear microsatellite markers. Previously, the presence of low and high Δ-3-carene pines has been demonstrated, but the results of the current study indicate that also diterpenoids form an independent axis of chemotypic differentiation. Further studies are needed to understand whether the enhanced abundance of diterpenoids in wetter sites reflects a phenotypic or genotypic response. Graphical abstract: Highlights: Isoabienol was the main diterpenoid alcohol in pine samples. Based on diterpenoid profiles we distinguished pine chemotypes. Needle contents of certain diterpenoids were related to foliar nitrogen contents. 'Manoyl oxide – isoabienol pines' were characteristic only to wetlands.